MENDETEKSI SECARA OTOMATIS OBJEK GERAKAN BERDASARKAN GAUSSIAN MIXTURE MODEL MENGGUNAKAN APLIKASI MATLAB - Aldina Syahfaridzah; Adelia Kartika Panggabean; Nabila Ayu Ardiningsih (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2020)
Automatically detects moving objects on a pedestrian video, each object will be detected by counting objects that appear at the beginning of the video based on a number. In detecting this object, the model used is the Gaussian Mixture Model whose performance is very effective if applied to any area that occurs in an object motion detected in the video. In this study, the Gaussian Mixture Model is used to model the background colors of each pixel. To facilitate the detection of this object, the Matlab 2016 application is also used, this application helps facilitate detection based on the size that will be adjusted according to the object to be detected.